2020
DOI: 10.1186/s12302-020-0299-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced soil aggregate stability limits colloidal phosphorus loss potentials in agricultural systems

Abstract: Background: Colloid-facilitated phosphorus (P) transport is recognized as an important pathway for the loss of soil P in agricultural systems; however, information regarding soil aggregate-associated colloidal P (P coll ) is lacking. To elucidate the effects of aggregate size on the potential loss of P coll in agricultural systems, soils (0-20 cm depth) from six land-use types were sampled in the Zhejiang Province in the Yangtze River Delta region, China. The aggregate size fractions (2-8 mm, 0.26-2 mm, 0.053-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…However, since most grasses (e.g., forages) take up about 40–70 kg P/ha per growing season and the final sampling date was at the beginning of the growing season on 4/13/20, it is unlikely that this led to an appreciable removal of soil P from the system. Thus, the most plausible explanation for the loss of P from the fire retardant-treated plots on this final sampling date after 71 cm of cumulative rainfall was leaching below 2.5 cm similar to the rationale provided by Hopmans et al It is likely the applied P moved below 2.5 cm via colloid-facilitated transport of P sorbed to clay particles. …”
Section: Resultssupporting
confidence: 61%
“…However, since most grasses (e.g., forages) take up about 40–70 kg P/ha per growing season and the final sampling date was at the beginning of the growing season on 4/13/20, it is unlikely that this led to an appreciable removal of soil P from the system. Thus, the most plausible explanation for the loss of P from the fire retardant-treated plots on this final sampling date after 71 cm of cumulative rainfall was leaching below 2.5 cm similar to the rationale provided by Hopmans et al It is likely the applied P moved below 2.5 cm via colloid-facilitated transport of P sorbed to clay particles. …”
Section: Resultssupporting
confidence: 61%
“…This confirms the conclusion drawn by other authors (Li et al, 2021; McLaren et al, 2014; Nakayama et al, 2021; Wei et al, 2022), who reported moderately labile Po as the P strongly associated with organic soil components. Furthermore, we also observed the distribution of moderately labile Po among aggregate was greatly associated with large aggregate than small aggregate because the aggregation promoted by organic matter counteracts the dispersion of the small mineral particles where P is retained (He et al, 2019; Li et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Soil aggregates regulate soil nutrient availability, influence soil pore composition, enhance soil structure and function, and enhance soil hydraulic properties (Fu et al., 2020; R. Wang et al., 2015; Whalen & Chang, 2002). The proportions of soil macroaggregates (>0.25 mm) indicate the stability of soil structure and soil structure, whereas the proportions of soil microaggregates (<0.053 mm) indicate the soil fertility status (Li et al., 2020; Liu et al., 2019). Therefore, we analyzed the distribution of different sizes (>0.25 and <0.053 mm) of water‐stable aggregates to assess soil physical crust stability.…”
Section: Methodsmentioning
confidence: 99%